Mathematical model of prognostication of the efficiency of the waste gas production for the develop-ment of strategy, complex of machines and equipment for handling hard domestic wastes - Bereziuk, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2013)
Parameters that influence the efficiency of the waste gas production in different countries are defined. The mathematical model of prognostication of the efficiency of the waste gas production is developed in the paper.